Food & feeding habits of an endemic carp, Osteobrama belangeri (Val.) in Manipur - Basudha, Ch; Viswanath, W (Indian Journal of Fisheries, 2011)
A total of 146 O. belangeri (V) of total length 6.0-25.9 cm and age group 0* to 4* year were sampled from different water sources. Their gut contents were analysed and buccopharynx studied. The percentage composition of major food items in various size groups of fish was different. In juveniles (6.-10 cm TL) zooplankton contents were the highest (51.9 %). Aquatic plants formed the main food item (40-60 %) in grownup fishes (10-26) cm TL). The alimentary canal is a long tube with undifferentiated stomach. The development of massive pharyngeal teeth reveals the capability of crushing hard bodied preys